2019
DOI: 10.1186/s12864-018-5352-z
|View full text |Cite|
|
Sign up to set email alerts
|

Genome analysis of Salmonella enterica subsp. diarizonae isolates from invasive human infections reveals enrichment of virulence-related functions in lineage ST1256

Abstract: BackgroundSalmonella enterica subsp. diarizonae (IIIb) is frequently isolated from the environment, cold-blooded reptiles, sheep and humans; however only a few studies describe the isolation of this subspecies from invasive human infections. The factors contributing to this unusual behavior are currently unknown.ResultsWe report here the genome features of two diarizonae strains, SBO13 and SBO27, isolated from endocervical tissue collected post-abortion and from cerebrospinal fluid of a newborn child, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…To date, there is therefore a stark gap in sampling and genome sequencing work that has been done on non-enterica subspecies. Previous reports indicate that non-enterica subspecies have lower invasive capacity, virulence, and levels of resistance to common antibiotics, and human infections have been mostly those involving weakened immune systems (15,59). However, as we have shown in this study, there is frequent recombination between subspecies, hence these less well-known subspecies likely act as reservoirs of novel allelic variants or genes that human-associated lineages can sample from when needed (e.g., as a response to environmental change or host immune system).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is therefore a stark gap in sampling and genome sequencing work that has been done on non-enterica subspecies. Previous reports indicate that non-enterica subspecies have lower invasive capacity, virulence, and levels of resistance to common antibiotics, and human infections have been mostly those involving weakened immune systems (15,59). However, as we have shown in this study, there is frequent recombination between subspecies, hence these less well-known subspecies likely act as reservoirs of novel allelic variants or genes that human-associated lineages can sample from when needed (e.g., as a response to environmental change or host immune system).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the comparative analysis of two Salmonella diarizonae strains isolated from invasive infections of humans, revealed that this Salmonella serotype pose a huge health-risk, as Giner-Lamia et al [52] identified in genomes of S. diarizonae strains a number of genes responsible for high virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Whether other substitutions in PagN di , such as the arginine or lysine at position 150 and 154 in loop 3 (Figure 1) modulate bacterial invasion remains to be determined. Like S. Typhi, S. diarizonae have type IVB pili involved in intestinal cell invasion, raising the possibility that the concomitant increased binding property of the S. diarizonae PagN allele contributes to the reported increased bacterial virulence in humans under specific conditions [5]. Taken together, the results showed that PagN alleles with a glutamic acid residue at either 49 or 109 improves bacterial binding and/or invasiveness, possibly due to the more ionizable and long chain characteristics of glutamic acid relative to aspartic acid and glutamine.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, some Salmonella such as S. enterica subsp. diarizonae (S. diarizonae) are primarily associated with cold-blooded animals, and only rarely result in invasive diseases in sheep or humans [5,6].…”
Section: Introductionmentioning
confidence: 99%